2018
DOI: 10.1016/j.mce.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based adverse outcome pathway approach for the identification of BPA as en endocrine disruptor in relation to its effect on the estrous cycle

Abstract: Proper cyclicity is essential to reach successful optimal fertility. In rats and mice, BPA exposure is repeatedly and reliably reported to show an adverse effect on the estrous cycle after exposures at different life stages. In humans, a possible association between modifications of menstrual cycle characteristics (e.g. length of the cycle, duration of menstrual bleeding) and sub-fecundity or spontaneous abortion has been observed. Alterations of ovarian cyclicity can therefore be definitely considered as an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 94 publications
1
9
0
Order By: Relevance
“…There are strong indications to link EDC exposure to POI, however, except for cigarette smoking, there is a lack of relevant human data addressing this [9]. Furthermore, disturbances of hormone levels-e.g., by BPA [10]-can cause menstrual cycle irregularities as well as affect the quantity and quality of available oocytes.…”
Section: Female Reproductive Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…There are strong indications to link EDC exposure to POI, however, except for cigarette smoking, there is a lack of relevant human data addressing this [9]. Furthermore, disturbances of hormone levels-e.g., by BPA [10]-can cause menstrual cycle irregularities as well as affect the quantity and quality of available oocytes.…”
Section: Female Reproductive Healthmentioning
confidence: 99%
“…It is clear though, that some EDCs can affect menstrual cyclicity. For example, an in-depth review clearly shows that an alteration of the HPG axis regulation of oestrogens by BPA is an essential mechanism underlying the observed menstrual cycle irregularities observed with BPA exposure [10]. Some studies show that the rate of folliculogenesis and steroidogenesis are reduced in women treated with ketoconazole during fertility treatment [31,32].…”
Section: Adulthoodmentioning
confidence: 99%
“…In adult rats, bisphenol A exposure can cause a decreased number of antral follicles and corpora lutea , as well as disrupted estrous cycle associated with delayed and lower amplitude LH surge (López-Rodríguez et al 2019 ). Numerous studies link bisphenol A exposure to aromatase inhibition in granulosa cells and delay or suppression of LH surge resulting in modified ovarian cyclicity (Viguié et al 2018 ). Di-(2-ethylhexyl) adipate can shorten the average length of the estrus cycle in rats (Wato et al 2009 ), whereas acetyl tributyl citrate has been shown to do so in mice (Rasmussen et al 2017 ).…”
Section: Adverse Outcome Pathways As They Relate To Key Processes In mentioning
confidence: 99%
“…However, exposure to low doses of BPA results in a variety of adverse effects in rodent in vivo and in vitro studies such as altered development of fetal testes tissue, decreased testosterone secretion in adult testis, altered ovarian cyclicity, and altered brain hormone levels and structure from developmental exposure (Richter et al 2007;Eladak et al 2015;Ullah et al 2018;Viguié et al 2018). Although the mechanism of action for BPA that leads to these effects is not entirely defined, it appears that BPA can act potently through nonclassical estrogen pathways (Alonso-Magdalena et al 2012) as well as alter expression of critical steroidogenesis enzymes such as aromatase (Viguié et al 2018). Even though the level of BPA in water is often too low to be captured in an EDA utilizing a bioassay based on binding to ERα and/or ERβ, that level may be biologically relevant to fish.…”
Section: Eac Modes Of Actionmentioning
confidence: 99%